A multicenter, prospective cohort study on the anti-SARS-CoV-2 vaccination response in patients with multiple sclerosis in Germany - Berthele, Achim; Gödel, Clemens; Kallmann, Boris-Alexander; Kowarik, Markus; Lehmann-Horn, Klaus; Marziniak, Martin; Rauer, Sebastian; Rothhammer, Veit; Bergh, Florian Then; Wahl, Mathias; Wildemann, Brigitte; Schirduan, Ksenija (Frontiers in Neurology, 2025)
BackgroundThis epidemiologic cohort study documented clinical and serological data in MS patients over several vaccination cycles against severe respiratory syndrome coronavirus-2 (SARS-CoV-2) in a real-world setting.MethodsAdult patients with MS were included during a period of 26 months from July 2021 if SARS-CoV-2 vaccination was planned, or first dose was given, or vaccination was completed within the last 6 weeks, or vaccination was completed >6 weeks ago and a booster dose was planned within the next 90 days. Humoral immune response to authorized SARS-CoV-2 vaccines was investigated during each vaccination cycle at baseline and approximately 1 and 6 months after vaccination. Immune response was defined as an anti-SARS-CoV-2 spike protein IgG titer >100 BAU/ml above pre-vaccination level and, separately, by the presence of SARS-CoV-2 neutralizing antibodies (NAb) approximately 1 month after the last vaccination.ResultsOf 159 patients enrolled, 140 (88.1%) were being treated with a DMT. Most patients (67.9%, n = 108) entered the study after complete initial SARS-CoV-2 vaccination (up to two doses) and before the 1st booster dose. Approximately 1 month after the 1st booster vaccination, response was seen in 68.1% of the patients (n = 79/116) based on anti-S1-IgG increase and in 72.1% (n = 88/122) based on NAb seropositivity. Persisting immune response approximately 6 months after vaccination was observed in 71.8% (n = 51/71) and in 93.7% (n = 74/79) of the responders, respectively. Adequate humoral immune response and persistence of response was less frequent in patients on anti-CD20 antibodies or sphingosine-1-phosphate receptor (S1PR) modulators compared to patients on other DMTs or DMT-untreated patients. Breakthrough infections with the SARS-CoV-2 virus were reported in 58 patients (36.5%). Seven patients (4.4%) experienced an MS relapse during the study period.ConclusionsWith the exception of anti-CD20 antibodies and S1PR modulators, DMTs did not impair humoral response to any of the authorized SARS-CoV-2 vaccines. Persistence of humoral immune response was seen over a period of at least 3 months in the majority of initial responders but was decreased in the anti-CD20 antibodies/S1PR modulator subgroup.Clinical trial registrationThis epidemiological study is registered in the German Clinical Trials Register (DRKS00025893).